Pengaruh Keragaman Produk dan Influencer Marketing Terhadap Keputusan Pembelian Produk Delice By Dite Kota Malang - Cindy Wahyu Amalia Putri; Yulis Nurul Aini; Fullchis Nurtjahjani (Indo Publishing, 2026)
Intense competition in the culinary sector has driven SMEs to continuously differentiate themselves and develop marketing strategies. Delice By Dite SME has responded by offering diverse products and collaborating with influencers. This study aims to analyze the influence of product diversity and influencer marketing on consumer purchasing decisions. This study employs a descriptive quantitative approach with variables including product diversity, influencer marketing, and purchasing decisions. Data was collected through purposive sampling from 94 respondents who are consumers of Delice By Dite and followers of the Instagram accounts @delicebydite and @quhin. Data analysis was conducted using multiple linear regression and hypothesis testing. The results of the study indicate that product diversity and influencer marketing had a positive and significant influence on the purchase decision of Delice By Dite’s products. Based on the research, it can be concluded that the greater the product diversity and the stronger the influence of influencers, the higher the consumer's tendency to make a purchase decision. Therefore, Delice By Dite is advised to increase product packaging variety and expand collaboration with various influencers whose audience base relevant to the target market.